Asymmetry of parametric x-ray radiation from polarized electrons (quantum approach) - Mazunin A. V. Andrey Vladimirovich; Potylitsyn A. P. Alexander Petrovich; Serdyutsky (Serdyutskiy, Serdjutsky, Serdyutskii) V. A. Vitaly Andreevich; Strikhanov M. N. Mikhail Nikolaevich (2001, 2001)
Title screen